Predictors of histological activity and fibrosis in chronic Hepatitis C infection: A study from North India - Singh Sompal; Gupta Ruchika; Malhotra Veena; Sarin Shiv (Wolters Kluwer Medknow Publications, 2010)
Background and Aims: The role of hepatitis C virus (HCV) genotypes in the severity of liver disease is still debatable and there is an occasional published report from India. The aim of this study is to assess the role of HCV genotypes in severity of liver disease in Indian patients. An attempt has also been made to perform a multivariate analysis to identify the predictors of severity of liver disease in chronic HCV infection. Materials and Methods: In this study, 31 newly diagnosed cases of chronic HCV infection over a period of two years were included. Age, sex and serum alanine transaminase (ALT) levels were recorded for each patient. HCV genotypes were identified using Line Probe assay (INNO-LiPA HCV II kit, Innogenetics, Belgium). Histological activity was graded and fibrosis was staged. Univariate and multivariate analysis was done to identify predictors of histological severity and fibrosis. Results: By univariate analysis, age of the patient, serum ALT levels and absence of genotype 3 (i.e., presence of HCV genotype other than genotype 3) showed association with histological activity score; whereas age and histological activity score showed association with fibrosis. However, on multivariate analysis, only serum ALT levels and absence of genotype 3 correlated well with activity score; while only activity score remained a significant predictor of stage of fibrosis. Conclusions: This study emphasizes the significant correlation of HCV genotype with severity of liver disease in chronic HCV infection. The stage of fibrosis showed correlation only with activity score as an independent factor. These results would further help in outlining algorithms for therapeutic stratification of patients with HCV infection.